Fabrication of PANI@Ti3C2Tx/PVA hydrogel composite as flexible supercapacitor electrode with good electrochemical performance. Issue 11 (1st June 2022) - Cao, Shuqing; Zhao, Tingkai; Li, Yatao; Yang, Lei; Ahmad, Adil; Jiang, Tao; Shu, Yuan; Jing, Zhuangmiao; Luo, Huijun; Lu, Xiaofeng; Zhang, Heng
Abstract: Developing a new strategy to effectively prevent the restacking of MXene nanosheets will have significant impacts on designing flexible supercapacitor electrodes. Herein, a novel Ti3 C2 Tx /polyvinyl alcohol (PVA) porous sponge with 3D interconnected structures is prepared by sol-gel and freeze-dried methods. This Ti3 C2 Tx /PVA porous sponge is used as the template of in-situ polyaniline (PANI) polymerization, and the fabricated PANI@Ti3 C2 Tx /PVA hydrogel composite is applied as flexible supercapacitors electrodes. 1D conductive polymer chains PVA could increase the interlayer spacing of Ti3 C2 Tx nanosheets, which is beneficial to expose more electrochemical active sites. The supercapacitor based on PANI@Ti3 C2 Tx /PVA hydrogel composite exhibits the coexistence of double-layer capacitance and pseudocapacitance behavior. This supercapacitor shows a maximum areal specific capacitance of 103.8 mF cm −2 at 2 A m −2, and it also exhibits a maximum energy density of 9.2 μWh·cm −2 and an optimum power density of 800 μW cm −2 . The capacitance of this supercapacitor is almost not change under different bending angles. Moreover, 99% capacitance retention is achieved after 10 000 charge/discharge cycles of the supercapacitor. The synergistic effect between PANI and Ti3 C2 Tx /PVA composite may improve the number of reactive sites and provide efficient channels for ion diffusion/electron transport.